Befriending Death: Henri Nouwen and a Spirituality of Dying - Twomey, Gerald S. (Cistercian studies quarterly, 2010)
The article reviews the book "Befriending Death: Henri Nouwen and a Spirituality of Dying," by Michelle O'Rourke.